The Anabasis of Patrick: Travelling an allegorical narrative map of illness and disability. (July 2018) - Monforte, Javier; Pérez-Samaniego, Víctor; Devís-Devís, José
Abstract: Objectives: This paper examines the stories of Patrick, a man living with cancer and a spinal cord injury. Design: An intrinsic case study was used to address Patrick's experiences. The design of the study is underpinned by narrative dialogism. Method: Photo-elicitation interviews were conducted. Visual and verbal data were analysed using a dialogical narrative analysis. Results: Patrick aligned his experiences with a story titled Anabasis to organize and express them. Although Anabasis is not a story about illness, it provides Patrick with an allegorical narrative map of how to live with disability and survive illness. Within 'The Anabasis of Patrick', the analysis identified three stages: walking back again, 'skipping stages of Anabasis' and surviving cancer. Throughout the course of his illness, Anabasis shapes how Patrick thinks and feels about his body and exercise, affecting his health behavior. A selection of images provided and discussed by Patrick illustrates the process of re-construction of his narrative self, and evokes the effects that Anabasis has on and for him. Conclusions: The study illuminates the key role narrative and storytelling hold regarding the (non)participation in exercise by people living with serious health problems. It also shows how visual metaphors represent embodied experiences in an effective, aesthetic and accessible manner, enhancing the knowledge dissemination process. To conclude, practical implications for exercise psychology and generalisations from the research are highlighted. Highlights: We study the case of a man living with life-threatening illness and disability. His narrative self is reconstructed in dialogue with a story titled Anabasis. Dialogical narrative analysis reveals how Anabasis acted as an allegorical narrative map of illness and disability. Visual metaphors enhance access and representation of embodied experiences. We discuss key developments of the research, practical implications for practitioners and generalizabilities.